Development of an Islamic Values Based Education Quality Management Model at Muhammadiyah Kalabahi Senior High School, Alor Regency, East Nusa Tenggara Province. - R.S., Abdullah; Prayitno, Irwan; Priharta, Andry (International Journal of Educational Narratives, 2025)
Background. Preliminary observations indicate that SMA-MK has not yet fully implemented AIK (Al-Islam and Kemuhammadiyahan) values. The AIK learning process does not yet adhere to Muhammadiyah guidelines; reference books are not specifically tailored to AIK content; AIK teachers are not Muhammadiyah cadres; the facilities and infrastructure supporting AIK learning are inadequate; and various other issues remain unresolved. Purpose. This study aims to examine the outcomes of developing a model, its feasibility, and the effectiveness of a quality management model based on Islamic values in SMA Muhammadiyah Kalabahi, Alor Regency, East Nusa Tenggara Province. Method. This research employed the Research and Development (R&D) method using the ADDIE model approach (Analysis, Design, Development, Implementation, Evaluation). Results. The findings of this study conclude that: (1) The development of a Quality Management Model based on Islamic values at SMA Muhammadiyah Kalabahi integrates the seven principles of quality management from ISO 9000 and the ten principles of Total Quality Management (TQM) by Goetsch & Davis (1994). This integration produces a final model consisting of five key dimensions: (a) focus on service quality; (b) engagement of all relevant stakeholders; (c) continuous improvement processes; (d) scientific approaches and proactive policies; (e) harmonious leadership and teamwork. Conclusion. Pragmatically, the model has brought about improvements in supporting facilities for AIK quality management, empowered AIK teachers, initiated and activated school-based Muhammadiyah autonomous organizations (such as IPM and HW), integrated AIK values with the multicultural values of the Alor community, and encouraged stronger school leadership commitment to AIK development as a means of institutionalizing Muhammadiyah culture and ideology in the school environment. The development of the Quality Management Model based on Islamic values at SMA Muhammadiyah Kalabahi achieved a feasibility score of 70.3%, indicating it is appropriate for implementation; The model demonstrated an effectiveness rate of 78%.